Subjective cognitive decline is associated with higher anxiety and depression during the COVID‐19‒related confinement. (31st December 2021) - Sánchez‐Benavides, Gonzalo; Akinci, Muge; Minguillón, Carolina; Deulofeu, Carme; Salvadó, Gemma; González‐de‐Echávarri, José María; Brugulat‐Serrat, Anna; Suarez‐Calvet, Marc; Sala‐Vila, Aleix; Grau‐Rivera, Oriol; Fauria, Karine; Molinuevo, Jose; et al.
Abstract: Background: Subjective cognitive decline (SCD) is often related to affective symptoms and both predict cognitive decline. We investigated whether SCD status predicted higher anxiety/depression during the Covid19‐related confinement, along with amyloid positivity in cognitively unimpaired older adults. Method: We included 205 participants from the ALFA+ study (Table 1). During the confinement, anxiety and depression (Hospital Depression and Anxiety scale, HADS), perceived stress (Perceived Stress Scale) and stress resilience (Brief Resilience Scale) were measured. Participants completed HADS, SCD‐Questionnaire, and underwent a [ 18 F]flutemetamol‐PET scan on average 2.4 years before confinement (baseline). We ran linear analyses with (i) cross‐sectional HADS scores during the confinement as well as (ii) change from baseline to confinement (delta scores) as dependent variables. SCD and amyloid status (+/‐, defined with a Centiloid threshold of 12) and their interaction were considered as predictors, and demographics, APOE‐ε4 status, and baseline HADS (for longitudinal analyses) as covariates. In a second step, perceived stress and stress resilience were considered in the models among covariates. Result: Twenty‐seven percent (n=56) of the participants were classified as SCD and 12.7% as amyloid positive. When main effects were tested, both SCD (p=0.03) and amyloid positivity (p=0.003) were associated with higher HADS scores during confinement (Table 2a). Further, a significant SCD*amyloid interaction was observed (p=0.001) such that only SCD participants with an amyloid positive scan showed higher HADS scores (p=0.001). SCD participants showed higher perceived stress than non‐SCD participants (p=.044), but no differences were found in stress resilience (p=0.6). The inclusion of perceived stress and stress resilience as covariates reduced the SCD effect to a trend (p=0.06) but not the effect of amyloid (p=0.003). Longitudinal analyses with delta scores showed similar results for amyloid but not for SCD main effects (Table 2b). The amyloid*SCD interaction was also significant in longitudinal analyses (p=0.002) with amyloid status predicting an increase in HADS scores only in participants with SCD (p=0.003) (Fig. 1). Conclusion: Having SCD and being amyloid positive is synergistically related to increased anxiety/depression during the Covid19‐related confinement. Longitudinal studies are warranted to investigate the impact of higher confinement related anxiety/depression in the clinical prognosis of the SCD population.